LFA - LOGISTIC FREIGHT ASSISTANCE USING HADOOP MAP REDUCE FRAMEWORK - Francis, Navya (IJRDO -Journal of Computer Science Engineering, 2015)
In recent years we are using the logistic freight system for the shipping of goods, and these shipping are done by thefreight forwarders/carriers from one point to the alternative point. Shipping charges are the freight bills, which has to be paid bythe specific organization after the delivery of freight. The freight forwarders/carriers can make mistakes during the preparation ofthe freight bills. Due to this accurate auditing of the bills has to be prepared otherwise the organization will have to overpay for theservices which they haven’t used. Now these auditing is done physically and it require lot of human power and time. Meanwhilethere is lot of chance for human and process errors. LFA (Logistic Freight Assistance) is the solution to these problems. It helps toaudit the freight bills and using LFA the stakeholders can make informed judgments. It overpowers the human and process errors.The system is developed based on the hadoop mapreduce framework. The data are stored in HDFS and processed using the hadoopmap reduce concept